Extraction of Chitin, Chitosan, and Calcium Acetate from Mussel Shells for Sustainable Waste Management - Seangarun, Chaowared; Seesanong, Somkiat; Boonchom, Banjong; Laohavisuti, Nongnuch; Rungrojchaipon, Pesak; Boonmee, Wimonmat; Punthipayanon, Sirichet; Thongkam, Montree (My University, 2025)
In this paper, mussel shells were used to produce chitin, chitosan, and calcium acetate using chemical processes, searching for an alternative environmentally friendly biopolymer and calcium source. Mussel shells were treated with acetic acid as a demineralizing agent, resulting in separate solid fractions and calcium solution. The solid was further purified to produce chitin by deproteinization and decolorization processes, and then the deacetylation process was used to obtain chitosan. The calcium solution was evaporated to produce calcium acetate powder. The yields of extracted chitin, chitosan, and calcium acetate from 100 g of mussel shells were 2.98, 2.70, and 165.23 g, respectively. The prepared chitin, chitosan, and calcium acetate were analyzed by Fourier transform infrared (FTIR) spectrophotometry, X-ray diffraction (XRD), thermogravimetric analysis (TGA), and scanning electron microscope (SEM) to confirm the chemical and physical properties. The analysis results of chitin and chitosan revealed the similarity to chitosan derived from crustaceans and insects in terms of functional group, structure and morphologies. The prepared calcium acetate shows FTIR and XRD data corresponding to calcium acetate monohydrate (Ca(CH3COO)2·H2O) similar to synthesized calcium acetate in previous research. In addition, the mineral contents of calcium acetate identified by X-ray fluorescence (XRF) analysis exhibit 97.8% CaO with non-toxic impurities. This work demonstrated the potential of the production process of chitin, chitosan, and calcium acetate for the development of a sustainable industrial process with competitive functional performance against the commercial chitin and chitosan production process using crustacean shells and supported the implementation of a circular economy.
Keywords: calcium acetate; chitin; chitosan; mussel shells; waste management